2021
DOI: 10.1051/0004-6361/202140449
|View full text |Cite
|
Sign up to set email alerts
|

Electron Bernstein waves and narrowband plasma waves near the electron cyclotron frequency in the near-Sun solar wind

Abstract: Context. Recent studies of the solar wind sunward of 0.25 AU reveal that it contains quiescent regions, with low-amplitude plasma and magnetic field fluctuations, and a magnetic field direction similar to the Parker spiral. The quiescent regions are thought to have a more direct magnetic connection to the solar corona than other types of solar wind, suggesting that waves or instabilities in the quiescent regions are indicative of the early evolution of the solar wind as it escapes the corona. The quiescent sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
0
17
3
Order By: Relevance
“…Regarding the generation mechanism, the observations presented in this work are inconclusive and do not favor any of the emission mechanisms proposed in Malaspina et al (2021). The present report on dependence on the magnetic field direction for the emission of the near-f ce harmonics is, to our knowledge, an unprecedented observation in the free solar wind plasma, which suggests that these waves may be connected to a distinctive, underlying property of the near-Sun environment.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Regarding the generation mechanism, the observations presented in this work are inconclusive and do not favor any of the emission mechanisms proposed in Malaspina et al (2021). The present report on dependence on the magnetic field direction for the emission of the near-f ce harmonics is, to our knowledge, an unprecedented observation in the free solar wind plasma, which suggests that these waves may be connected to a distinctive, underlying property of the near-Sun environment.…”
Section: Discussioncontrasting
confidence: 72%
“…In this study, similar to earlier studies, we could not identify the generation mechanism of the nearf ce harmonics waves. Different mechanisms have been suggested: electron cyclotron drift instability, loss-cone instability, electromagnetic pump wave, and wave-wave interaction (Malaspina et al 2021). The observations reported in this study, that the waves favor a particular range of magnetic field directions, do not support any of the previously proposed wave generation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, an instability related to the sunward deficit itself could operate, as suggested by Berčič et al (2021b). Malaspina et al (2021) also discussed a loss cone instability driven by sunward electrons as a candidate to generate narrowband plasma waves observed by PSP near the Sun.…”
Section: The Occurrence Of the Sunward Deficitmentioning
confidence: 96%
“…As a result, Malaspina et al (2020) conclude that a near-radial ambient magnetic field, though necessary, is not a sufficient condition for the growth of near-f ce waves. Earlier studies have suggested that near-f ce harmonic structures are composed of electron Bernstein waves, and at least two other wave modes that have not been completely identified so far (Malaspina et al 2020;Ma et al 2021;Malaspina et al 2021;Shi et al 2022). The generation mechanism of these waves is still an open question.…”
Section: Introductionmentioning
confidence: 95%